Penerapan Mind Mapping dalam Pembelajran Writing Bahasa Inggris di MTs. Alwashliyah - Chairunnisa, Chairunnisa; Fahada, Nazli (Center of Knowledge : Jurnal Pendidikan Dan Pengabdian Masyarakat, 2025)
This community service program aimed to enhance the writing skills of students at Mts. Alwashliyah by applying the mind mapping technique. The primary objective was to assist students in organizing their thoughts and generating structured written content. The method involved a series of workshops, practical sessions, and evaluations. The students were first introduced to the concept of mind mapping, followed by hands-on practice sessions to apply the technique in their writing exercises. The program utilized pre-tests and post-tests to assess the effectiveness of the intervention. The results showed a significant improvement in students' writing performance. After implementing mind mapping, students demonstrated better organization, richer vocabulary, and enhanced creativity in their written texts. The post-test scores increased by an average of 20% compared to the pre-test results, indicating a positive impact of the technique on their writing abilities. In conclusion, mind mapping proved to be an effective strategy for improving students' writing skills by helping them systematically organize their ideas. This technique not only enhanced their writing competence but also boosted their confidence in expressing themselves. The program’s success highlights the potential for broader application in other educational settings to support English language learning.